DOMESTIC ENERGY UTILIZATION AND POTENTIALS OF ALTERNATIVE SOURCES OF ENERGY IN MUBI METROPOLIS - Bulus Luka Gadiga; Kevin Ferdinand Jigumtu; Hajjatu Tammi (Department of Geography Education, University of Jember, 2018)
The Study investigates domestic energy utilization and potentials of alternative sources of energy in Mubi metropolis of Adamawa State. To achieve the objectives of this study, data were collected using questionnaire. A total of 108 sets of questionnaire were retrieved and analyse using descriptive statistics. Some of the data collected from respondents include; types of energy used for various purposes, factors that influence such use and preferences for the different types of energy. Other information which cannot be collected using questionnaire were obtained from published and unpublished materials. The findings show that households rely more on fuel-wood. Economic factors were found to influence the choice of energy used in homes. Solar energy and wind energy have high potentials as alternative energy source that will help in mitigating climatic change. The study concludes that households in Mubi metropolis tend to climb the energy ladder from low grade energy types to modern energy when income increases and such energy are made available. The study recommends that households be sensitized on the health and environmental effects of traditional energy. Households should be encouraged to use modern and alternative sources of energy in order to mitigate climate change. Such energies should also be made affordable and available since majority of the respondents were willing to switch when made affordable. Keywords: Domestic energy, alternative energy, climate change, firewood. References CBN (2009). Statistical Bulletin, Central Bank of Nigeria: Volume 20, December 2009 Climate Change Network Nigeria (CCNN, 2003) Monitoring Nigerian climate change. www.ccnnigeria.org accessed on February, 2018 DECC, (2013) The UK low carbon transition plan: national strategy for climate and energy. Presented to Parliament pursuant to Sections 12 and 14 of the Climate Change Act 2008, TSO ETB (2011) Engineering Tool Box. http://www.engineeringtoolbox.com. Accessed May 2017 Federal Ministry of Environment (2014). Nigeriaâ€™s Second National Communication Under TheUnited Nations Framework Convention on Climate Change. Abuja, Nigeria. Halava, Satu (2013) Carbon Footprint of Thermowood. unpublished project, Satakunnan University of Applied Sciences. Accessed on 13th August, 2018 from https://www.theseus.fi/bitstream/handle/10024/63624/Halava_Satu.pdf;sequence=1 Kaltimber (2017) How much CO2 is stored in 1 kg of wood? http://www.kaltimber.com/blog/2017/6/19/how-much-co2-is-stored-in-1-kg-of-wood accessed on 11th August, 2018. Mshelia, A. D (2015). Seasonal Variations of Household Solid Waste Generation in Mubi, Nigeria. International Journal of Innovative Education and Research. Vol. 3, No. 5 Momodu I. M., (2013). Domestic Energy Needs and Natural Resources Conservation: The Case of Fuelwood Consumption in Nigeria. Mediterranean Journal of Social Sciences, Vol 4 No 8. 27-33 NEC, (2006) National Emission Ceilings for Certain Atmospheric Pollutants. Ministry of Housing, Spatial Planning and the Environment, The Hague, Netherlands New, M., Bruce Hewitson, David B. Stephenson, Alois Tsiga, Andries Kruger â€¦.Robert Lajoie (2006): Evidence of trends in daily climate extremes over southern and West Africa, J. Geophys. Res., 111, D14102, doi: 10.1029/2005JD006289. Nigeria Energy Commission, (2006) Report of survey of energy utilization in the informal sector: A case study of the FCT, Federal Ministry of Power Technical Report. September, 2006. Obueh, J. (2008), â€œThe Ecological Cost of increasing Dependence on Biomass fuels as Household Energy in Rural Nigeriaâ€: Lessons from Boiling Point No. 44, GTZ/ITDG. Laurent Cousineau copyright 2011-2017, climate change guide. Osueke C. O and C. A. K. Ezugwu (2011) Study of Nigeria Energy Resources and Its Consumption. International Journal of Scientific & Engineering Research, Vol. 2, (12) Oyeneye O.O., (2004) Socio-economic influence on policies of Power Deregulation, Proc 20th National Conference of the Nigeria Society of Engineering (Electrical Division), October 6th to 7th, 2004, Pp.1-15 Palmer J, Cooper I. (2014) United Kingdom energy housing fact file 2013; 2014. Union of Concerned Scientists (UCS), (2015) Science for a healthy planet and safer world. 2016â€“2020 Strategic Plan World Bank, (2005).â€˜â€˜Household Energy Use in Developing Countriesâ€™â€™ (series No.5). Washington D.C., U.S.A: retrieved on August 16, 2012 from ESMAP Report.http://www.Worldbank.org./esmap/. Accessed on July 10th, 2012. Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License